Treatment of ichthyosis lamellaris using a series of herbal skin care products family - Tirant, M; Bayer, P; Hercogovấ, J; Fioranelli, M; Gianfaldoni, S; Chokoeva, A A; Tchernev, G; Wollina, U; Novotny, F; Roccia, M G; Maximov, G K; França, K; et al. (Journal of biological regulators and homeostatic agents, 2016)
Lamellar ichthyosis (LI) is a genetically heterogeneous group of disorders of keratinization that are inherited in an autosomal recessive fashion, occurring in approximately 1 in 300,000 live births. The treatment of the large, dark, plate-like scales that characterize the classic manifestation of the disease are still a challenge. The aim of this study was to evaluate the efficacy and tolerability of Dr. Michaels® skin-care products for the management of LI. A multi-centre European prospective study was conducted, including 10 patients (3 female/7 male) with lamellar ichthyosis, aged 38-54 years old (mean age: 46). Each patient had been treated with emollients plus other different systemic therapies, such as corticosteroids, Cyclosporin A or retinoids in the past. All patients were treated with Dr Michaels® product family including both topical and oral herbal supplements. The topical treatments used were the cleansing gel, activator formula and ointment. The oral medications were PSC 200, PSC 400 and PSC 900. Within 3 weeks of initiation of treatment, there were improvements observed on the skin including a reduction in scaling, fissuring, and intensity in erythema and pruritus with thinning of the hyperkeratotic plate. After 12-15 weeks, most of the plates and scales had been removed to reveal a normalised skin colour. Evidence of hair, eyelash and eyebrow growth was observed. There was partial nail resolution with a reduction in subungual hyperkeratosis. No adverse reactions were observed. Our patients showed excellent symptomatic response to treatment within a 14-week period, follow-up by an on-going regular assessment on a quarterly basis. The results show that Dr Michaels® product family is an effective and safe treatment option for LI.
Keywords: Phytotherapy; potravní doplňky; péče o kůži; Middle Aged; mužské pohlaví; Prospective Studies; Adult; fytoterapie; ženské pohlaví; lamelární ichtyóza; Humans; prospektivní studie; Skin Care; Dietary Supplements; Skin; lidé středního věku; Ointments; dospělí; Female; Ichthyosis, Lamellar; kůže; lidé; Male; masti